2008
DOI: 10.1089/vbz.2007.0271
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Diseases in North Carolina: Is“Rickettsia amblyommii”a Possible Cause of Rickettsiosis Reported as Rocky Mountain Spotted Fever?

Abstract: Cases of Rocky Mountain spotted fever (RMSF) in North Carolina have escalated markedly since 2000. In 2005, we identified a county in the Piedmont region with high case numbers of RMSF. We collected ticks and examined them for bacterial pathogens using molecular methods to determine if a novel tick vector or spotted fever group rickettsiae (SFGR) might be emerging. Amblyomma americanum, the lone star tick, comprised 99.6% of 6,502 specimens collected in suburban landscapes. In contrast, Dermacentor variabilis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
186
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(196 citation statements)
references
References 34 publications
5
186
0
5
Order By: Relevance
“…30 More recently, a group in North Carolina obtained serum samples from patients considered probable cases of RMSF and found that some of the patients had higher end-point titers against R. amblyommii antigen than R. rickettsii . 11 In our study, the most common rickettsial species in all sexes and stages of ticks was R. amblyommii . The finding of R. amblyommii in the A. americanum larval pools indicates that transovarial transmission of R. amblyommii may be occurring.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…30 More recently, a group in North Carolina obtained serum samples from patients considered probable cases of RMSF and found that some of the patients had higher end-point titers against R. amblyommii antigen than R. rickettsii . 11 In our study, the most common rickettsial species in all sexes and stages of ticks was R. amblyommii . The finding of R. amblyommii in the A. americanum larval pools indicates that transovarial transmission of R. amblyommii may be occurring.…”
Section: Discussionmentioning
confidence: 57%
“…8,9 Rickettsia amblyommii , in particular, has been suggested as a potential cause of high SFGR seroprevalence. 10,11 Little is known about the diversity and prevalence of SFGR in ticks in Tennessee because of spatial and technical limitations of previous studies. In 1974 Burgdorfer and others 12 identified R. rickettsii in D. variabilis in the Land Between the Lakes area bordering Kentucky by examining hemolymph, which is not as reliable for species identification as modern molecular techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Although different strains of R. amblyommii have been reported to infect different tick species of the New World (Labruna 2009, Castellaw et al 2010, Ogrzewalska et al 2010, Bermúdez et al 2011, the pathogenicity of R. amblyommii in humans remains to be demonstrated. Interestingly, there is serological evidence suggesting that it is a human pathogen in the United States (Apperson et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Lone star tick pathogens include the long-implicated Rickettsia rickettsii, the agent of RMSF [25,26]; Francisella tularensis, the agent of tularemia; Ehrlichia chaffeensis, Ehrlichia ewingii, Panola Mountain Ehrlichia; [3] and other rickettsial organisms including R. parkeri and R. amblyommii [3]. The latter is now suspected of being a mild pathogen and may contribute to cross-reactivity when testing for R. rickettsii [3,27]. A newly identified lone star tick-vectored virus commonly called Heartland virus has caused 2 deaths and 5 other cases in the Midwest and South [28].…”
Section: Discussionmentioning
confidence: 99%